(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: This study aims to describe of the results of internal medical treatment of seminal vesiculitis at the Center for andrology and sexual medicine, Viet Duc Hospital of University. Materials and methods: Retrospective descriptive study with longitudinal follow-up was conducted on 60 patients diagnosed with seminal vesiculitis who received outpatient medical treatment at Viet Duc Hospital of University from January 2021 to the end of June 2022. Results: The average age of subjects was 43.5 ± 10.8 (21-67). The most common clinical symptoms were bloody ejaculation and painful ejaculation with rates of 98.33% and 40% respectively. The negative rate of urine culture was 90%. Positive semen culture results were: 16/60 (26.67%). Average follow-up time: 15.9 ± 5.4 months. Treatment results: cure: 61.67%, relapse: 36.67%. There was stasistically significant difference regards of the treatment success rate between the positive semen culture and the negative group (p=0.01). Conclusion: Medical treatment of seminal vesiculitis is a method that gives positive results but is also prone to recurrence. Semen culture test can be of great benefit for treatment.